Monte-Carlo determination of adiabatic compressibility of hard spheres. Issue 12 (12th August 2020) - Grigoriev, A. N.; Kleshchonok, T. V.; Markov, I. V.; Bulavin, L. A.
ABSTRACT: We analyze numerical methods for the determination of the adiabatic compressibility of fluids in computer experiments. Some of them like the Monte-Carlo (MC) method in constant pressure ensembles can be applied for particles which interact through hard-core potentials. We calculate adiabatic compressibility and sound velocity at different pressures for the hard-sphere fluid using conventional MC method in two ensembles: isothermal and adiabatic (isothermal-isobaric and isobaric-isoenthalpic). We show that the accuracy of adiabatic compressibility of the hard-sphere fluid is the same both for the isobaric-isoenthalpic and isothermal-isobaric- ensembles.